2022
DOI: 10.3390/cancers14112780
|View full text |Cite
|
Sign up to set email alerts
|

Interconnected Adaptive Responses: A Way Out for Cancer Cells to Avoid Cellular Demise

Abstract: Different from normal cells, cancer cells must hyperactivate a variety of integrated responses in order to survive their basal stress or its exacerbation caused by exposure to anti-cancer agents. As cancer cells become particularly dependent on these adaptive responses, namely UPR, DDR autophagy, anti-oxidant and heat shock responses, this turns out to be an Achille’s heel, which allows them to be selectively killed while sparing normal unstressed cells. Better knowledge of the cross-talk between these adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Towards this aim, we used GSK2606414 (GSK), 4μ8C, and CeapinA7, drugs known to inhibit PERK, IRE1α/XBP1, and ATF6, and found that all of them efficiently inhibited their targets, p-EIF2α, XBP1s, and BIP, respectively ( Figure 1 A). The inhibition of all three UPR sensors affected BL cell survival ( Figure 1 B) while it did not affect that of primary B lymphocytes ( Figure S1 ), according to the knowledge that normal cells are less dependent than cancer cells on UPR activation for their survival [ 12 ]. However, 4μ8C, the IRE1α/XBP1 inhibitor, was more efficient against Akata and Oma 5, as BL36 cells displayed sensitivity to 4μ8C similar to that induced by GSK and CeapinA7 ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Towards this aim, we used GSK2606414 (GSK), 4μ8C, and CeapinA7, drugs known to inhibit PERK, IRE1α/XBP1, and ATF6, and found that all of them efficiently inhibited their targets, p-EIF2α, XBP1s, and BIP, respectively ( Figure 1 A). The inhibition of all three UPR sensors affected BL cell survival ( Figure 1 B) while it did not affect that of primary B lymphocytes ( Figure S1 ), according to the knowledge that normal cells are less dependent than cancer cells on UPR activation for their survival [ 12 ]. However, 4μ8C, the IRE1α/XBP1 inhibitor, was more efficient against Akata and Oma 5, as BL36 cells displayed sensitivity to 4μ8C similar to that induced by GSK and CeapinA7 ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, XBP1s have the capacity to upregulate the expression of several molecules involved in DDR, either belonging to Homologous Repair (HR) and non-homologous end joining (NHEJ) repair. The cross-talk between UPR and DDR has been extensively reviewed [ 11 ] and we have recently contributed to dissect the relationship between these as well as the other adaptive responses that sustain the survival of cancer cells [ 12 ]. Based on this background, in this study, we investigated the impact of UPR inhibition on BL cell survival, focusing on IRE1α which is known to be the more important UPR sensor for the survival of a variety of hematological cancers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy, targeted therapy, immunotherapy, and radiotherapy are currently the most frequently used types of tumor therapy. However, doctors and researchers continue to face difficulties with the resistance of the majority of patients to chemotherapeutic drugs, immune checkpoint inhibitors, and targeted medicines [ 34 ]. Resistance mechanisms include the aberrant expression of membrane transport proteins such as ATP-binding cassette transport proteins and P-glycoprotein, altered drug metabolic pathways, DNA repair, autophagy, hypoxic tumor microenvironments, enhanced stemness of tumor stem cells, mutations in epidermal growth factor receptor genes, and T cell depletion [ 35 , 36 ].…”
Section: Autophagy and Tumormentioning
confidence: 99%
“…Several processes have been implicated in the development of chemoresistance, particularly those able to promote adaption to proteotoxic or genotoxic stress, such as autophagy, unfolded protein response (UPR), DNA damage response (DDR), antioxidant response, and heat shock response (HSR). In this regard, recent studies have revealed that these responses are interconnected and that the inhibition of one of them can either inhibit or activate the other/s [6]. In the latter case, the concomitant inhibition of several adaptive responses is required to obtain a better therapeutic outcome compared to the inhibition of the single process, while in the former case, such cross-talk can be exploited to render cancer cells more sensitive to treatments.…”
Section: Introductionmentioning
confidence: 99%